2022
DOI: 10.1177/19322968221124583
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Intelligence for Predicting and Diagnosing Complications of Diabetes

Abstract: Artificial intelligence can use real-world data to create models capable of making predictions and medical diagnosis for diabetes and its complications. The aim of this commentary article is to provide a general perspective and present recent advances on how artificial intelligence can be applied to improve the prediction and diagnosis of six significant complications of diabetes including (1) gestational diabetes, (2) hypoglycemia in the hospital, (3) diabetic retinopathy, (4) diabetic foot ulcers, (5) diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 95 publications
1
28
0
1
Order By: Relevance
“…Similarly, diabetes is a leading cause of death and its management as another chronic disease requires a novel approach to improving patients’ prognosis. In this field, the use of artificial intelligence has been tested to enhance the prediction and diagnosis of significant complications of diabetes leading to adverse cardiovascular events 20 . This is of particular interest in the field of gestational diabetes and recent research has identified the possibility of using a dedicated machine learning approach to improve its prediction 21 …”
Section: Artificial Intelligence In Cardiovascular Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, diabetes is a leading cause of death and its management as another chronic disease requires a novel approach to improving patients’ prognosis. In this field, the use of artificial intelligence has been tested to enhance the prediction and diagnosis of significant complications of diabetes leading to adverse cardiovascular events 20 . This is of particular interest in the field of gestational diabetes and recent research has identified the possibility of using a dedicated machine learning approach to improve its prediction 21 …”
Section: Artificial Intelligence In Cardiovascular Preventionmentioning
confidence: 99%
“…In this field, the use of artificial intelligence has been tested to enhance the prediction and diagnosis of significant complications of diabetes leading to adverse cardiovascular events. 20 This is of particular interest in the field of gestational diabetes and recent research has identified the possibility of using a dedicated machine learning approach to improve its prediction. 21 In the management of dyslipidaemia, different potential applications of artificial intelligence have been tested so far, starting from the diagnosis to the management and prognosis related to the disease.…”
Section: Management Of Cardiovascular Risk Factors (Arterial Hyperten...mentioning
confidence: 99%
“…The incidence of DR is primarily related to the course of diabetes and the degree of disease control. The longer the course of diabetes, the higher the incidence of DR ( Huang et al, 2023 ). At present, the pathogenesis of DR is unclear, but glucose metabolism disorder is the root cause of DR ( Han et al, 2023 ).…”
Section: Application Of Artificial Intelligence In Retinal Vascular D...mentioning
confidence: 99%
“…These words were searched for in the title, abstract, and keywords. Moreover, to refine the search scope, the most employed ML and DL techniques were identified based on Huang et al 8 These techniques were examined using the authors' keywords. The search was restricted to English articles and reviews published between 2000 and 2022.…”
Section: A Search Strategymentioning
confidence: 99%
“…[2][3][4][5] These AI-driven approaches use computational algorithms to analyze complex data sets, identify patterns, and develop predictive models that can contribute to early diagnosis, personalized treatment, and effective management strategies for people with diabetes. [6][7][8] Over time, AI-based tools have also been used to enhance aspects of diabetes education, such as prediction, dietary and exercise guidance, carbohydrate counting, insulin dose guidance, monitoring of complications, and selfcontrol. 9 These advancements highlight the potential of AI to revolutionize the approach to diagnosing, treating, and educating individuals about this disease.…”
Section: Introductionmentioning
confidence: 99%